2016
DOI: 10.1182/blood-2015-09-618553
|View full text |Cite
|
Sign up to set email alerts
|

Beyond hydroxyurea: new and old drugs in the pipeline for sickle cell disease

Abstract: Despite Food and Drug Administration (FDA) approval of hydroxyurea to reduce the frequency of vaso-occlusive episodes, sickle cell disease (SCD) has continued to be treated primarily with analgesics for pain relief. However, elucidation of the multiple pathophysiologic mechanisms leading to vaso-occlusion and tissue injury in SCD has now resulted in a burgeoning effort to identify new treatment modalities to prevent or ameliorate the consequences of the disease. Development of new drugs as well as investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 88 publications
0
98
0
Order By: Relevance
“…Despite high efficacy, disease activity and mortality remain high in patients taking HU (1), with the life expectancy of SCD patients in the United States still estimated to be 20 years less than that of individuals without the disease (37). It is imperative to identify new treatments to prevent and better manage systemic vaso-occlusive pain crisis, to increase the quality and quantity of life for SCD patients (38). Based on our findings and the recent work of other investigators, targeting adhesion molecules on platelets and/or neutrophils to prevent or disintegrate neutrophil-platelet aggregates can be a promising therapy for SCD patients, particularly for the prevention of acute chest syndrome in high-risk patients presenting with systemic vaso-occlusive pain crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite high efficacy, disease activity and mortality remain high in patients taking HU (1), with the life expectancy of SCD patients in the United States still estimated to be 20 years less than that of individuals without the disease (37). It is imperative to identify new treatments to prevent and better manage systemic vaso-occlusive pain crisis, to increase the quality and quantity of life for SCD patients (38). Based on our findings and the recent work of other investigators, targeting adhesion molecules on platelets and/or neutrophils to prevent or disintegrate neutrophil-platelet aggregates can be a promising therapy for SCD patients, particularly for the prevention of acute chest syndrome in high-risk patients presenting with systemic vaso-occlusive pain crisis.…”
Section: Discussionmentioning
confidence: 99%
“…100 A recent phase 1B dose-escalation study of 26 HbSS and HbS/b 0 -thalassemia patients found that SCD-101 was well tolerated and, at higher doses, it seemed to relieve chronic pain and fatigue but had no impact on Hb levels or hemolysis. 101 The review by Telen 3 lists only a single antisickling agent undergoing clinical trials that is known to directly modify Hb structure: 5-hydroxymethyl-furfural (Aes-103). This agent is an aldehyde that forms a reversible Schiff base linkage primarily with the N-terminal amino group of a-globin resulting in a dose-dependent increase in oxygen affinity.…”
Section: Anti-polymerization Drugs Currently In Clinical Trialsmentioning
confidence: 99%
“…In addition, sickle rbc are more adherent to the vascular endothelium than normal rbc (8), which may further contribute to VOC and hemolysis. Adhesive interactions lead to formation of heterocellular aggregates that obstruct blood flow to induce ischemic tissue damage, which leads to the prolonged exposure of rbc to deoxygenated conditions, promoting further HbS polymerization and hemolysis (9).…”
Section: Introductionmentioning
confidence: 99%